Impression Management, Fairness, and the Employment Interview - Rosenfeld, Paul (Journal of business ethics, 1997)
This paper contends that impression management is not inherently a threat to fairness in employment interviews. Rather, regarding impression management as unfair is based on an outdated, narrow view of impression management as conscious, manipulative, and deceptive. A broader, expansive model of impression management is described which sees these behaviors as falling on a continuum from deceptive and manipulative on the one hand, to accurate, positive and beneficial on the other. While organizations may want to eliminate or discount the negative aspect of the impression management continuum, the ability to positively 'sell' oneself is often a desirable attribute both in the employment interview and in later on-the-job settings. This expansive view of impression management contends that organizations can make employment interviews more fair by: viewing impression management as a skill and not a deficit, training interviewers to be wary of manipulative and deceptive impression management, reducing the ambiguity and uncertainty of interview settings and increasing the verifiability of candidate responses by focusing the interview on a candidate's long-term identities and accomplishments rather than their short-term, spur-of-the-moment attempts to please the interviewer.